Design, Synthesis, Biological Evaluation, and X‐ray Studies of HIV‐1 Protease Inhibitors with Modified P2′ Ligands of Darunavir. (24th November 2017) - Ghosh, Arun K.; Fyvie, W. Sean; Brindisi, Margherita; Steffey, Melinda; Agniswamy, Johnson; Wang, Yuan‐Fang; Aoki, Manabu; Amano, Masayuki; Weber, Irene T.; Mitsuya, Hiroaki
Abstract: The structure‐based design, synthesis, and biological evaluation of a series of nonpeptidic HIV‐1 protease inhibitors with rationally designed P2′ ligands are described. The inhibitors are designed to enhance backbone binding interactions, particularly at the S2′ subsite. Synthesis of inhibitors was carried out efficiently. The stereochemistry of alcohol functionalities of the P2′ ligands was set by asymmetric reduction of the corresponding ketone using ( R, R )‐ or ( S, S )‐Noyori catalysts. A number of inhibitors displayed very potent enzyme inhibitory and antiviral activity. Inhibitors3g and3h showed enzyme K i values of 27.9 and 49.7 pm and antiviral activity of 6.2 and 3.9 nm, respectively. These inhibitors also remained quite potent against darunavir‐resistant HIV‐1 variants. An X‐ray structure of inhibitor3g in complex with HIV‐1 protease revealed key interactions in the S2′ subsite. Abstract : Structured antivirals : We report the structure‐based design, synthesis, biological evaluation, and X‐ray structural studies of a series of highly potent HIV‐1 protease inhibitors containing novel P2′ ligands to interact with protease active site residues. The inhibitors were designed to enhance backbone binding interactions, particularly at the S2′ subsite. A number of inhibitors displayed very potent enzyme inhibitory and antiviral activity and remained quite potent against darunavir‐resistant HIV‐1 variants. X‐ray crystallographic work revealed key interactions in the S2′ subsite.